Strategy of Disruptive Innovation in Emerging Regional Markets: Factors of Success and Failure - Vertakova, Yuliya V.; Rudakova, Olga V.; Shadrina, Valentina V.; Kobersy, Iskandar S.; Belova, Irina N. (International Journal of Economics and Financial Issues, 2016)
Disruptive innovation opens up new technological cycle and a new cycle of business innovation, because it is not intended to support the existing and established core technology, with strong well-established company in this market, and it aims to completely change the technology radically to undermine the market. Each of the above concepts of innovation in their own way successfully draws attention to is actually the same phenomenon-change of technological cycles or economic cycles, the depth of the changes in the economic system. Therefore, they can be considered as homogeneous, interchangeable concepts. This article is devoted to analysis of formation and development of “disruptive” innovation. We analyzed the factors of success and failure “disruptive” strategies. On the basis of experience in the development of disruptive strategies based on demand creation, a comparison of innovative models being implemented in various industry markets. Keywords: disruptive innovations, developing countries, demand, production cycle, technology, disruptive strategy, innovative product JEL Classifications: O30, Q55, O18, R11